A systematic review on the validated measures used to assess anxiety in Malaysia - Abdul Khaiyom, Jamilah Hanum; Mukhtar, Firdaus; Tian, Po Ooi (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
The current study aims to investigate the validated measures used to assess anxiety in Malaysia through a systematic review. The PsycINFO and MEDLINE databases, and 28 local journals were used to search for published papers in this particular area. Twenty articles met the inclusion criteria and reviewed. The results showed that majority of the studies have validated self-report inventories, rather than structured clinical interviews. The preferred measures validated were Depression Anxiety and Stress Scale, Hospital Anxiety and Depression Scale, and General Health Questionnaire-12 item. The psychometric properties of the validated measures were also reported in this review. In general, the measures have a wide range of reliability, validity, and factor structures. However, not all of the studies adhere to the standard procedures for adapting Western-based measure. The limitations of the studies under review were also being highlighted.